BRAFV600E induces ABCB1/P-glycoprotein expression and drug resistance in B-cells via AP-1 activation. Issue 11 (November 2015) - Tsai, Yo-Ting; Lozanski, Gerard; Lehman, Amy; Sass, Ellen J.; Hertlein, Erin; Salunke, Santosh B.; Chen, Ching-Shih; Grever, Michael R.; Byrd, John C.; Lucas, David M.
Highlights: A new inducible cell line system was used to determine targets of mutant BRAF in B-cells. One such target is ABCB1 /P-gp, suggesting the use of BRAF pathway inhibitors with therapies that include P-gp substrates. Abstract: A subset of patients with chronic lymphocytic leukemia (CLL) and nearly all patients with classic hairy cell leukemia (HCL) harbor somatic BRAF activating mutations. However, the pathological role of activated BRAF in B-cell leukemia development and progression remains unclear. In addition, although HCL patients respond well to the BRAF V600E inhibitor vemurafenib, relapses are being observed, suggesting the development of drug resistance in patients with this mutation. To investigate the biological role of BRAF V600E in B-cell leukemia, we generated a CLL-like B-cell line, OSUCLL, with doxycycline-inducible BRAF V600E expression. Microarray and real-time PCR analysis showed that ABCB1 mRNA is upregulated in these cells, and P-glycoprotein (P-gp) expression as well as function were confirmed by immunoblot and rhodamine exclusion assays. Additionally, pharmacological inhibition of BRAF V600E and MEK alleviated the BRAF V600E -induced ABCB1 /P-gp expression. ABCB1 reporter assays and gel shift assays demonstrated that AP-1 activity is crucial in this mechanism. This study, uncovers a pathological role for BRAF V600E in B-cell leukemia, and provides further evidence that combination strategies with inhibitors of BRAF V600E and MEK can be used to delay disease progression and occurrence of resistance.